A distinct brain beta amyloid signature in cerebral amyloid angiopathy compared to Alzheimer's disease. (14th May 2019) - Gkanatsiou, Eleni; Portelius, Erik; Toomey, Christina E.; Blennow, Kaj; Zetterberg, Henrik; Lashley, Tammaryn; Brinkmalm, Gunnar
Highlights: Distinct difference in Aβ peptide pattern in subjects with and without CAA. Aβ peptides ending at amino acid 42 are more abundant in AD subjects with no CAA. Aβ peptides ending at amino acid 40 are more abundant in CAA subjects. Abstract: Cerebral amyloid angiopathy (CAA) is a type of vascular disease present in more than 50% of demented elderly and more than 80% of Alzheimer's disease (AD) patients. Both CAA and AD are characterized by extracellular Aβ deposits with the distinction that CAA has vascular deposits while AD has amyloid plaques. In this study, we used immunoprecipitation (IP) in combination with mass spectrometry (MS) to test the hypothesis that the Aβ peptide pattern differs between subjects having Aβ plaque pathology only and subjects with Aβ plaque pathology together with CAA pathology. Occipital lobes from 12 AD brains, ranging from no CAA to severe CAA, were extracted using 70% formic acid followed by IP-MS analysis. The Aβ peptide pattern differed greatly between subjects with no CAA compared to subjects with CAA. In cases with CAA, the most abundant Aβ peptides ended at amino acid 40 including Aβ1-40 (P = .048) and Aβ 2–40 (P = .0253) which were significantly increased compared to cases with no CAA. This was in contrast to subjects with no CAA where the most abundant Aβ peptides ended at amino acid 42 of which Aβ1-42 (P = .0101) and Aβ2-42 (P = .0051) as well as the pyroglutamate (pGlu)-modified peptides pGlu Aβ3-42 (P = .0177), and pGlu Aβ11-42 (P = .0088) were significantly increased compared to CAA subjects. The results are in line with earlier immunohistochemistry data and show that the molecular composition of the Aβ deposits found in blood vessels are different to the parenchymal deposits, suggesting they arise from distinct pathogenic pathways. This information may be useful in the development of pathology-specific biomarkers.